A companion to the war film - Cunningham, Douglas A. 1969-; Nelson, John C. 1938- (Wiley Blackwell, 2016)
"A Companion to the War Film contains 27 original essays that examine all aspects of the genre, from the traditional war film, to the new global nature of conflicts, to the diverse formats war stories assume in today's digital culture"...